Relationship between brachial plexus injury and intensive care unit-managed COVID-19 patients requiring prone ventilation: A scoping review - Tuta-Quintero, Eduardo; Collazos, Estefania; Molina, Miguel Angel; Pimentel, Juan; Santander Ruiz Ramos, Jesús; Roncancio Forero, Kamila; Santodomingo Vásquez, Jesús Rafael; Ramírez Ortega, Martín Andrés (Revista Cubana de Medicina Tropical, 2024)
Introduction: Brachial plexus neuropathy is a rare complication of therapeutic pronation at the intensive care unit. Few studies explore the association between ICU-managed COVID-19 and the development of plexopathies of the upper limbs. Objective: Synthesize the medical literature on the relationship between COVID-19 requiring prone ventilation and brachial plexus neuropathy. Methods: A scoping review including observational studies in PubMed and Scopus. Results were summarized based on the general characteristics of each included article. Results: Eleven full-text articles were included, identifying case series (n = 4), case reports (n = 3), retrospective (n = 2) and prospective (n = 2) cohort studies, with a total sample of 361 patients. The brachial plexus injury is a rare complication of prone ventilation in the ICU. Males with a history of high blood pressure, diabetes mellitus and obesity are more likely to develop this injury. The main clinical manifestations were weakness, paresthesia, and neuropathic pain with an onset time from one to four weeks after the end of pronation. Conclusion: Prone ventilation in the treatment of patients with severe COVID-19 has been increasing along with neurological complications such as brachial plexus neuropathy.